2015
DOI: 10.1186/s13045-015-0131-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel vaccine for mantle cell lymphoma based on targeting cyclin D1 to dendritic cells via CD40

Abstract: BackgroundMantle cell lymphoma (MCL) is a distinct clinical pathologic subtype of B cell non-Hodgkin’s lymphoma often associated with poor prognosis. New therapeutic approaches based on boosting anti-tumor immunity are needed. MCL is associated with overexpression of cyclin D1 thus rendering this molecule an interesting target for immunotherapy.MethodsWe show here a novel strategy for the development of recombinant vaccines carrying cyclin D1 cancer antigens that can be targeted to dendritic cells (DCs) via CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…published a study recently on a novel vaccine for mantle cell lymphoma targeting cyclin D1 while Dragnev et al . focused on its role as adjuvant in the treatment of aerodigestive tract tumours . To our knowledge, our results are novel regarding cyclin D1 expression in FDCS and its presence should be considered further as both a supportive diagnostic marker and potential therapeutic target in FDCS.…”
Section: Discussionmentioning
confidence: 80%
“…published a study recently on a novel vaccine for mantle cell lymphoma targeting cyclin D1 while Dragnev et al . focused on its role as adjuvant in the treatment of aerodigestive tract tumours . To our knowledge, our results are novel regarding cyclin D1 expression in FDCS and its presence should be considered further as both a supportive diagnostic marker and potential therapeutic target in FDCS.…”
Section: Discussionmentioning
confidence: 80%
“…The overall beneficial effect was potentiated by co-administration of rituximab [213]. Chen et al, 2015 have developed a novel vaccine based on targeting Cyclin D1 to Dendritic cells (DC) via the human DC surface receptor CD40 to elicit Cyclin D1-specific T cells, which is being tested in in vivo models [214]. Newer clinical trials have been designed to evaluate the clinical efficiency of some of these novel antibodies and vaccines (Table 3).…”
Section: Novel Drugs For MCL Based On Signaling Pathwaysmentioning
confidence: 99%
“…With the proper antigen presentation to cytotoxic T cells, cancer cells can be targeted similarly to old or virally infected cells. Cyclin D1, a frequently upregulated cyclin in mantle cell lymphoma has been singled out as an effective antigen for vaccination therapy 163 . The frequent over expression of cyclin D1 in mantle cell lymphoma and its potency in T cell activation upon cross presentation contribute to why cyclin D1 makes an excellent target for vaccines 163 .…”
Section: Targeting the Immune Cell Populations Using Vaccines And mentioning
confidence: 99%
“…Cyclin D1, a frequently upregulated cyclin in mantle cell lymphoma has been singled out as an effective antigen for vaccination therapy 163 . The frequent over expression of cyclin D1 in mantle cell lymphoma and its potency in T cell activation upon cross presentation contribute to why cyclin D1 makes an excellent target for vaccines 163 . Along other lines, Mattarollo et al showed that a cancer antigen cocktail with an α–galactosylceramide (α-GalCer) adjuvant could successfully activate natural killer T cells against B cell lymphoma and subsequently inhibit its growth in mice lymphoma models 164 .…”
Section: Targeting the Immune Cell Populations Using Vaccines And mentioning
confidence: 99%